Increased state of activation of CD4 positive T cells and elevated interferon γ production in pouchitis. Issue 4 (1st October 1998) - Stallmach, A; Schäfer, F; Hoffmann, S; Weber, S; Müller-Molaian, I; Schneider, T; Köhne, G; Ecker, K-W; Feifel, G; Zeitz, M
Abstract : Background —Immunoregulatory abnormalities of T cells might be of importance in the pathogenesis of pouchitis after ileoanal pouch anastomosis (IAP). Aims —To characterise T cell subsets, their state of activation, and production of cytokines in inflamed and non-inflamed pouches in patients with ulcerative colitis (UC) and familial adenomatous polyposis (FAP). The influence of T cell activation on mucosal transformation was also studied. Patients —Mucosal biopsy specimens were taken from 42 patients with IAP (33 with UC and nine with FAP). Methods —Mononuclear cells were isolated by standard techniques and characterised by three colour flow cytometry. Interferon γ (IFN-γ) production was studied using the ELISPOT technique. Results —In patients with UC with pouchitis there was a significant increase in the CD4:CD8 ratio, expression of activation markers on CD3+ cells, and number of IFNγ producing mononuclear cells compared with patients with UC without pouchitis (CD4:CD8 ratio 1.3 (range 0.7–2.7) versus 0.6 (0.1–1.0), p=0.012). In addition, a positive correlation between increased crypt depth and the number of CD4+ cells ( r =0.57) was shown. Conclusion —The observed increase in activated mucosal CD4+ T cells and IFN-γ production might lead to mucosal destruction and crypt hyperplasia as seen in pouchitis.